On one existence and uniqueness theorem - Kibenko, A.; Chepurnowa, L. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. В. Кибенко, Л. Г. Чепурнова. Об одной теореме существования и единственности A. Kibenko, L. Čepurnova. Apie vieną egzistencijos ir vienetinumo teoremą